Tongue Conditions in Reproductive Disorders: Indicators of Qi Deficiency and Imbalance - Kustiyati, Sri; Mintara, Arya Yoga; Kusumadewi, Rita Riyanti (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2025)
Tongue diagnosis in Traditional Chinese Medicine (TCM) serves as a non-invasive diagnostic tool for assessing overall health by evaluating the tongue’s color, shape, coating, and moisture. This study aims to analyze the tongue characteristics of patients with reproductive system disorders to explore potential diagnostic correlations. This study employs a quantitative descriptive research method with a descriptive observational design, involving 82 patients from the Holistic Consultation Group who sought treatment for reproductive health issues. Tongue assessments were conducted through direct visual observation, categorizing color, shape, coating, and moisture levels, followed by statistical analysis using frequency distribution. Tongue color: 59.8% (49 patients) had pale tongues, suggesting blood or energy deficiencies. Tongue shape: 79.3% (65 patients) had thick tongues, indicating digestive and metabolic issues. Tongue coating: 57% (47 patients) had thick coatings, associated with internal dampness or phlegm accumulation. Tongue moisture: 93.9% (77 patients) had moist tongues, suggesting excess fluids or weak digestion. The findings highlight a significant correlation between tongue characteristics and reproductive health disorders, reinforcing the potential of tongue diagnosis as a supplementary assessment tool in holistic healthcare. Further research integrating tongue analysis with biomedical diagnostics is recommended to enhance its clinical applicability.